The Role of Foreign Ownership in The Implementation of Green Economy in Hospitality Companies in Indonesia - Yeni Ekowati; Ni Putu Eka Widiastuti; Sri Mulyantini (Green Publisher Indonesia, 2023)
The contribution of the tourism sector to the Indonesian economy is still less than 5%, even though this sector has a considerable multiplier effect. The Covid-19 pandemic has made this sector struggle to maintain its business. Green economy is an idea that is guided by people, planet, & profit and began to be discussed in various countries in the last period of time to realize sustainable business development. The purpose of this study is to evaluate the role of foreign ownership in moderating CSR activities and implementing green products in hospitality companies in Indonesia. Considering that foreign parties are more concerned about environmental issues and business sustainability. The research used was a quantitative method with a research sample of 38 hospitality companies listed on the Indonesia Stock Exchange in 2020 with moderated regression analysis. The results of this study show that foreign ownership is able to moderate CSR activities, but has not been able to moderate the implementation of green products on the value of hospitality industry companies in Indonesia. The results of this study can be taken into consideration for hospitality company management to formulate the right strategy to increase firm value.